Investigations of the Electronic Structure and Bandgap of the Next‐Generation LED‐Phosphor Sr[LiAl3N4]:Eu2+—Experiment and Calculations. Issue 4 (2nd January 2015) - Tolhurst, Thomas M.; Boyko, Teak D.; Pust, Philipp; Johnson, Neil W.; Schnick, Wolfgang; Moewes, Alexander
<x xml:space="preserve">Abstract</x> The electronic structure of recently reported nitridolithoaluminate Sr[LiAl3N4]:Eu2+ determined through soft X‐ray spectroscopy measurements and density functional theory calculations is discussed. With its high emission intensity in the red region of the electromagnetic spectrum and its uniquely narrow bandwidth for an Eu2+‐doped phosphor, this breakthrough material shows great potential for use in illumination‐grade pc‐LEDs. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>